Clip Ligation and Disconnection of a Ruptured Ventral Subaxial Cervical Isolated Spinal Aneurysm Using Tailored Access Osteotomies: An Operative Technique. Issue 4 (28th April 2023) - Scullen, Tyler; Ng, Christina; Mathkour, Mansour; Tubbs, R. Shane; Bui, Cuong; Kalyvas, James
Abstract : BACKGROUND: Isolated spinal aneurysms (iSAs) are lesions of the spinal vasculature with no associated vascular malformation with difficult management paradigms limited by safe access. OBJECTIVE: To describe a case of an irregular fusiform ruptured distal subaxial cervical spine iSA with a complex angioarchitecture intimately associated with the ventral pial plexus (VPP), treated using open clip ligation and disconnection. METHODS: A 51-year-old woman presented with complete spinal cord injury with a C8 sensory level and ventral subarachnoid hemorrhage at the C6-T1 vertebral levels. After emergent anterior evacuation and fusion, angiography revealed a small iSA around the VPP. A total laminectomy spanning C5 to T3 was completed, and bilateral C7 pedicle resections were performed. A temporary clip was placed from the left for proximal control, and a permanent clip was placed across the dome of the distal vessel for disconnection. The dura was then closed, and a cervicothoracic fusion completed. RESULTS: Postoperative angiography confirmed iSA disconnection and obliteration with anterior spinal artery preservation. The patient had intermittent numbness in the right C8 dermatome. On postoperative day 1, she regained proprioception in the right foot and movement in the lower extremities on command. On postoperative day 3, she regained full sensation and voluntary movement in both lower extremities. CONCLUSION: iSA is a rare and morbid condition with nonstandardized guidelines regarding management. We promote the concept of using tailored osteotomies to establish safe corridors for the open treatment of difficult subaxial cervical ventral lesions not amenable to transarterial treatment. Multidisciplinary collaboration is promising, and further investigation is highly warranted.